Empowering decision makers in Latin America: potential impact of three interventions for tobacco control - Alcaraz, Andrea (2018)
Background: The burden of disease attributable to tobacco use in Latin America is very high. The objective of this study was to evaluate the potential impact of implementing cigarette plain packaging (PP), 100% smoke-free environments (SFE) and complete ban on advertising, promotion and sponsorship of tobacco (BAPS) in Argentina, Bolivia, Brazil, Chile, Colombia, Mexico and Peru. Methods: A mathematical model was used to estimate the chances people have to get sick or die because of 17 smoking-related conditions. A systematic review was carried out to identify the epidemiological and cost data relevant to each country, as well as the effectiveness of the interventions. The model considered each country's legislation and level of compliance for each intervention. Then, we modeled the expected impact on health and costs of different potential scenarios for these interventions. Results: We estimated the following benefits for all seven countries: PP could avoid 204 073 deaths, 212 867 cardiovascular events, 26 456 cancer diagnoses, 99 784 COPD cases, and 23 739 USD on direct medical costs in the next ten years. 100% SFE could lead to avoid 150 361 deaths, 247 171 cardiovascular events, 77 400 cancers and 311 129 COPD cases, and 15 413 USD on direct medical costs in the next ten years. 100% BAPS could save 86 911 deaths, 327 390 cardiovascular events, 38 883 cancers, 142 104 COPD cases, and 10 505 USD on direct medical cost to the health system in the next ten years. Different scenarios were modeled for each country. An example-the case for Colombia- is shown in the table. Conclusions: The potential impact of fully implementing PP, 100% SFE and BAPS could avoid a large burden of disease and costs for the health systems in Latin America. This information could be useful for decision makers to promote these policies.